Transport chain choice modelling in freight transport demand models - Huber, Stefan (Open Science Journal, 2017)
Modelling (intermodal) transport chains is of major relevance in order to support public sector decision-making regarding transport planning and policy measures assessment. However, the systematic and comprehensive analysis of freight transport models shows that only few existing models integrate transport chain choice in their modelling framework. These models, furthermore, differ in consideration of relevant aspects – such as actors, processes, transport market interactions or shipment and system related characteristics. The analysis reveals that there are several gaps in integrating transport chains in modelling in today’s modelling approaches and that there is no model that integrates all relevant aspects of transport chain choice properly. Future research and model development should therefore focus on closing the revealed gaps.